Optimal gate commutated thyristor design for bi-mode gate commutated thyristors underpinning high, temperature independent, current controllability - Lophitis, N.; Antoniou, M.; Vemulapati, U.; Vobecky, J.; Badstuebner, U.; Wikstroem, T.; Stiasny, T.; Rahimo, M.; Udrea, F. (My University, 2018)
The bi-mode gate commutated thyristor (GCT) is an advanced reverse conducting device aiming high-power applications. Due to the high degree of interdigitation of diode parts and GCT parts, it is necessary to investigate how to best separate the two and at the same time, how to maximize the individual power handling capability. This work underpins the latter, for the GCT part. In achieving that, this letter details the optimization direction, identifies the design parameters that influence the maximum controllable current (MCC), and thereafter introduces a new design attribute, the 'p-zone.' This new design not only improves the MCC at high temperature but also at low temperature, yielding temperature independent current handling capability and at least 1000 A, or 23.5% of improvement compared to the state-of-the-art. As a result, the proposed design constitutes an enabler for optimally designed bi-mode devices rated at least 5000 A for applications with the highest power requirement.
Keywords: Full wafer modeling; gate commutated thyristor; maximum controllable current; MCC; reverse conducting